A Sensor of Protein O‐Glycosylation Based on Sequential Processing in the Golgi Apparatus. (31st October 2012) - Bachert, Collin; Linstedt, Adam D.
Abstract : Protein O‐glycosylation is important in numerous processes including the regulation of proteolytic processing sites by O‐glycan masking in select newly synthesized proteins. To investigate O‐glycan‐mediated masking using an assay amenable to large‐scale screens, we generated a fluorescent biosensor with an O‐glycosylation site situated to mask a furin cleavage site. The sensor is activated when O‐glycosylation fails to occur because furin cleavage releases a blocking domain allowing dye binding to a fluorogen activating protein. Thus, by design, glycosylation should block furin from activating the sensor only if it occurs first, which is predicted by the conventional view of Golgi organization. Indeed, and in contrast to the recently proposed rapid partitioning model, the sensor was non‐fluorescent under normal conditions but became fluorescent when the Golgi complex was decompartmentalized. To test the utility of the sensor as a screening tool, cells expressing the sensor were exposed to a known inhibitor of O‐glycosylation extension or siRNAs targeting factors known to alter glycosylation efficiency. These conditions activated the sensor substantiating its potential in identifying new inhibitors and cellular factors related to protein O‐glycosylation. In summary, these findings confirm sequential processing in the Golgi, establish a new tool for studying the regulation of proteolytic processing by O‐glycosylation, and demonstrate the sensor's potential usefulness for future screening projects .